Faktor yang Mempengaruhi Perilaku Pembelian Produk Makanan Impor Berlogo Halal di Batam - Stella, Stella; Zai, Immanuel (Penerbit Goodwood, 2025)
Purpose: This study aims to identify the factors that influence purchase behavior, with a specific focus on how purchase intention acts as a mediator in this relationship. The study investigates the roles of brand trust, customer satisfaction, product attributes, and religiosity in shaping consumers' purchasing actions toward imported food products. Methodology/approach: The research was conducted using a quantitative approach through an online survey. A total of 309 respondents who had experience purchasing imported food products were selected using purposive sampling. Data was collected through a structured questionnaire and analyzed using statistical methods to assess the relationships between the variables. Results/findings: The results reveal that product attributes, brand trust, customer satisfaction, and religiosity significantly influence purchase intention. Furthermore, purchase intention positively and significantly affects purchase behavior. However, several variables, such as brand trust and customer satisfaction, showed directions of influence that were contrary to the initial hypotheses, suggesting the presence of contextual or external moderating factors. Conclusions: Purchase intention plays a crucial mediating role in linking key factors such as brand trust, satisfaction, attributes, and religiosity with actual purchasing behavior. Enhancing these factors can strengthen consumer intentions and lead to increased purchase activity. Limitations: he study is limited to consumers of imported halal-labeled food products in Batam and may not be generalizable to other age groups, regions, or product categories. Contribution: This research contributes to the field of consumer behavior and marketing by offering insights into the psychological and attitudinal factors that drive purchase behavior.